The chondrichthyan community of Maranhao (Northeastern Brazil) II : biology of species - Menni, Roberto Carlos (1998)
Fil: Menni, Roberto Carlos. División Zoología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina